Engagement Session between UMPSA, MoHE, industry and strategic partners strengthens national economy - Rosidah, Hassan (UMPSA, 2024)
KUALA LUMPUR, 6 May 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently held an Engagement Session with the Ministry of Higher Education (MOHE), industry and strategic partners and agencies to gain ideas, exchange knowledge, find out current issues in the industry and agencies, and create career opportunities, further strengthening the relationship between academia and industry players and agencies.